HEAVY METAL CONTENT IN SOME SEAFOODS COLLECTED FROM MUARA ANGKE FISH AUCTION PLACE, JAKARTA. - Hutagalung, Horas; Syamsu, Suwirma (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1987)
Determination of heavy metal content (Hg, Pb, Cd, Cu, Cr, Zn) in some seafoods collected from Muara Angke Fish Auction Place were carried out during February to July 1979. The results showed that Zn content in seafoods a nalyzed was always much higher than the other heavy metals. The concentration levels of the six heavy metals observed were low. It is almost of the same level as the metal concentration of other seafoods observed in various parts of the world oceans, but still lower than the maximum standard set for human consumption as established by Tasmania, Australia and World Health Organization. The mean per capita consumption of fish in Jakarta is only about 165 g per week, while the Provisional Tolerated Weekly Intake for Hg, set by WHO/FAO at 300 ug level, would be attained by consuming 1500 g Rastrelliger sp., or 698 gPenaeus setiferus, or 545 g Sepia sp., and or 1250 g Pecten sp. Therefore, at present the level of metal content in fishes sold at TPI Muara Angke can be considered as not dangerous to human health as long as these quantities are not surpassed.